DYNAMICS OF COGNITIVE DEVELOPMENT OF DYSLEXIA STUDENTS THROUGH MULTISENSORY LEARNING - Fatimah, Nur; Ansyah, Eko Hardi; Ghozali Rusyid Affandi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the dynamics of cognitive development of dyslexic students with multisensory interventions. Based on research conducted in Surabaya in 2019, it was shown that 37% of children from 7 schools in Surabaya have dyslexia. The large percentage is the basis for the importance of finding effective interventions for dyslexic children. One strategy that can be done is through multisensory interventions. The multisensory method is a method that introduces the concept of learning by maximizing the sensory that is owned. Method: The type of research used in the study is a qualitative case study study with a subject of a male student in grade 2 of elementary school in Sidoarjo. The data collection method in the study used triangulation methods including interviews, observations, and documentation. Results: The results of this study indicate that the application of multisensory interventions to children with dyslexia can have a positive influence on psychological development in the cognitive domain. Novelty: The use of the case study method involving research subjects is intended as a novelty from previous research in order to obtain the latest data regarding its effectiveness.